Brachybacterium epidermidis Sp. Nov., a Novel Bacterial Species Isolated from the Back of the Right Hand, in a 67-Year-Old Healthy Woman. (29th March 2022) - Boxberger, Manon; Magnien, Sibylle; Antezack, Angéline; Rolland, Clara; Makoa, Marine; La-Scola, Bernard; Cassir, Nadim
Abstract : Knowledge on human skin microbiota composition has been expanding in recent years. Its role in human health and disease represents an active area of investigation. As part of our culturomics project that consists of exploring the human microbiota by isolating bacteria through innovative culture-dependent methods, we isolated a new bacterial strain from the back of the right hand, in a 67-year-old healthy woman. Here, we characterize the strain Marseille-Q2903 by the taxonogenomic approach. Marseille-Q2903 exhibits a 99.5% 16S rRNA sequence similarity with Brachybacterium muris T but with only 92% of coverage. The closest species based on a 100% coverage of the 16S sequence is Brachybacterium timonense T with an identity similarity of 97.63%. Furthermore, digital DNA-DNA hybridization reveals a maximum identity similarity of only 31.5% and an OrthoANI parameter provided a value of 86.95% between Marseille-Q2903 and Brachybacterium muris T . Marseille-Q2903 is a yellowish-pigmented, Gram-positive, coccoid shaped, and facultative aerobic bacterium, and belonging to the Dermabacteraceae family. The major fatty acids detected are 12-methyl-tetradecanoic acid (69%), 14-methyl-hexadecanoic acid (16%), and 14-methyl-pentadecanoic acid (7%). Marseille-Q2903 genome size is of 3, 073, 790 bp, with a 70.43% G + C content. Taken altogether, these results confirm the status of this strain as a new member of the Brachybacterium genus for which the name of Brachybacterium epidermidis sp. strain Marseille-Q2903 T is proposed (=CSURQ2903 T  = CECT30363).